Cerebral Venous Sinus Thrombosis, a Nonenhanced CT Diagnosis?. (11th May 2015) - Alsafi, Ali; Lakhani, Amish; Carlton Jones, Lalani; Lobotesis, Kyriakos
Abstract : Purpose . Retrospectively evaluate the density of cerebral venous sinuses in nonenhanced head CTs (NCTs) and correlate these with the presence or absence of a cerebral venous sinus thrombus (CVST). Materials and Methods. Institutional review board approval was obtained and informed consent waived prior to commencing this retrospective study. Over a two-year period, all CT venograms (CTVs) performed at our institution were retrieved and the preceding/subsequent NCTs evaluated. Hounsfield Units (HUs) of thrombus when present as well as that of normal superior sagittal and sigmoid sinuses were measured. HU of thrombus was compared to that of normal vessels with and without standardisation to the average HU of the internal carotid arteries. Results . 299 CTVs were retrieved, 26 with a thrombus. Both raw and standardised HU measurements were significantly higher in CVST (p < 0.0001 ) compared to normal vessels. Both raw and standardised HUs are good predictors of CVST. A HU of ≥67 and a standardised measurement of ≥1.5 are associated with high probability of CVST on NCT. Conclusion. Cerebral venous sinus HU measurements may help improve sensitivity and specificity of NCT for venous sinus thrombosis and avoid potentially unnecessary follow-up examinations.